2019
DOI: 10.1002/jbmr.3901
|View full text |Cite
|
Sign up to set email alerts
|

HR-pQCT Measures of Bone Microarchitecture Predict Fracture: Systematic Review and Meta-Analysis

Abstract: High‐resolution peripheral quantitative computed tomography (HR‐pQCT) is a noninvasive imaging modality for assessing volumetric bone mineral density (vBMD) and microarchitecture of cancellous and cortical bone. The objective was to (1) assess fracture‐associated differences in HR‐pQCT bone parameters; and (2) to determine if HR‐pQCT is sufficiently precise to reliably detect these differences in individuals. We systematically identified 40 studies that used HR‐pQCT (39/40 used XtremeCT scanners) to assess 129… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(62 citation statements)
references
References 69 publications
3
51
0
3
Order By: Relevance
“…In older men, the presence of fragility fractures was also associated with lower Tb.N, Ct.Th, and Ct.BMD and increased Ct.Po [ 50 , 51 ] and a conversion from plates into rods [ 52 ]. In a recent systematic review and meta-analysis, radial and tibial HR-pQCT parameters, including failure load, were significantly lower, ranging from − 2.6 to − 12.6%, in subjects with a prior fracture [ 53 ].…”
Section: Hr-pqct and Fracturementioning
confidence: 99%
“…In older men, the presence of fragility fractures was also associated with lower Tb.N, Ct.Th, and Ct.BMD and increased Ct.Po [ 50 , 51 ] and a conversion from plates into rods [ 52 ]. In a recent systematic review and meta-analysis, radial and tibial HR-pQCT parameters, including failure load, were significantly lower, ranging from − 2.6 to − 12.6%, in subjects with a prior fracture [ 53 ].…”
Section: Hr-pqct and Fracturementioning
confidence: 99%
“…There is a paucity of data on bone microarchitecture assessed invasively or noninvasively using imaging modalities in patients with MFS. In a systematic review and meta‐analysis including 40 studies using HR‐pQCT and evaluating fracture risk, Mikolajewicz and colleagues ( 22 ) reported that total vBMD, trabecular vBMD, as well as cortical vBMD and cortical thickness were reliable predictors of fractures. Furthermore, Hansen and colleagues ( 23 ) found that trabecular number and spacing, cortical thickness, and cortical area correlates moderately to very highly with the maximum compressive strength of the hip.…”
Section: Discussionmentioning
confidence: 99%
“…( 2 ) In the past decade, application of HR‐pQCT for clinical research has grown rapidly, with a strong focus on the assessment of osteoporotic fracture risk. ( 3,4 ) This is in large part because HR‐pQCT provides additive information to dual‐energy X‐ray absorptiometry (DXA), ( 4,5 ) by including the assessment of bone microarchitecture, an important determinant in bone strength.…”
Section: Introductionmentioning
confidence: 99%